Signatures of exposure to childhood trauma in young adults in the structure and neurochemistry of the superior temporal gyrus. (May 2023) - Hepsomali, Piril; Machon, Sandra; Barker, Holly; Lythgoe, David J; Hugdahl, Kenneth; Gudbrandsen, Maria; Allen, Paul
Background: Childhood trauma (CT) has been linked to increased risk for mental illness in adulthood. Although work in experimental animals has shown that early life stressors can affect inhibitory and excitatory neurotransmission in adult rodents, with possible excitotoxic effects on local grey matter volumes (GMV), the neurobiological mechanisms that mediate this relationship in humans remain poorly understood. Aim: To examine glutamate and gamma-aminobutyric acid (GABA) metabolite concentrations and potential excitotoxic effects on GMV, in adults who experienced CT. Methods: Fifty-six young adults ( M age = 20.41) were assigned to High CT ( n = 29) and Low CT ( n = 27) groups (by using the CT questionnaire) and underwent magnetic resonance spectroscopy ( 1 H-MRS) to measure temporal lobe metabolite concentrations and volumetric imaging to measure GMV. Results: Glutamate concentrations did not differ between groups; however, relative to the Low CT group, participants in the High CT group had reduced GABA concentrations in the left superior temporal gyrus (STG) voxel. Furthermore, logistic regression showed that participants with low left STG GABA concentrations and low left STG volumes were significantly more likely to be in the high CT group. Conclusions: This study provides the first evidence that both low GABA concentrations and its interaction with GMV in the left STG are associated with high levels of CT and suggest that altered inhibitory neurotransmission/metabolism may be linked to a lower GMV in the left STG in adults who experienced CT. Future studies are warranted to establish if utilizing these measures can stratify clinical high-risk and predict future clinical outcomes in high CT individuals.